The influence of cold filaments on the evolution of dipole structures - Yang, Qi; Wang, Guihua; Xu, Chi; Gao, Guoping; Sun, Ruili (Frontiers in Marine Science, 2023)
Mesoscale eddy dipoles are oceanographic structures that can transport ocean water parcels horizontally and vertically in ways that differ from individual mesoscale eddies. The most conspicuous additional feature that presents in dipoles is the cold filament (CF) that can be spontaneously generated between a dipole’s anticyclonic eddy (AE) and cyclonic eddy (CE). A case study in this paper shows that the interaction between the CF and the CE component of the dipole is associated with the structural evolution of the dipole. This interaction is verified in synthesis and normalization studies of the CF dipoles. The CF-dipole interaction entrains CF water into the center of the dipole’ CE and leads to a cold and high chlorophyll center in the upper layer of the CE. The formation of this cold center changes the dipole’s structure by eliminating the phase difference between the thermal and dynamic centers of the dipole. The entrainment also provides a new mechanism for the development of high chlorophyll levels in the CE. In the analysis of the HYCOM (Hybrid Coordinate Ocean Model) simulation of a synthetic CF dipole, the AE has a three-zone structure while the CE only has two. The convergence of the CE’s outermost zone results in a biased interaction.